Demons and the Making of the Monk: Spiritual Combat in Early Christianity. By David Brakke - Vivian, Tim (The journal of theological studies, 2007)
WithDemons and the Making of the Monk, David Brakke continues his study of early Egyptian monasticism begun in his Athanasius and the Politics of Asceticism (Oxford University Press, 1995). In the earlier book, Brakke was interested in monasticism primarily as a tool in Athanasius’ ecclesiastical designs, while here, with Demons and the Making of the Monk, he goes deeper, leaving the surface of church politics to rappel down into the depths of early monastic spirituality and demonology (the two cannot be separated). Whether he discovers here a rocky, dry riverbed or a gardened valley may depend on his reader's attitude towards demons and demonology. I found the landscape breathtaking, both fertile and challenging.